PENERAPAN TEKNOLOGI TEPAT GUNA (TTG) MESIN GRANULATOR DAN SCREW UNTUK MENINGKATKAN KUALITAS PRODUKSI PUPUK [THE IMPLEMENTATION OF APPROPRIATE TECHNOLOGY GRANULATOR AND SCREW MACHINES TO IMPROVE THE QUALITY OF FERTILIZER PRODUCTION] - Andhika Cahyono Putra; Mohammad Muslimin (Jurnal Sinergitas PKM & CSR, 2018)
The aims of this activity (Program Kemitraan Masyarakat - PKM) was to improve the quality product trough transferring knowledge into appropriate technology (Teknologi Tepat Guna -TTG) in term of production. This program has two partners, Mr. Masdukin’s small industries in Fertilizer and Mrs. Munthoipah's cake industry. Both partners located in Pakis Village, Trowulan – East Java. The main Problem from the first partners were (i) The stirring engines fertilizer could not work maximally and restrain the production. The root problem was the cutting place is too long, it needs to be modified in order to work maximum, (ii) The results fertilizers produced in the form of soil, whereas it should be having maximum benefit if the fertilizer production in the form of pellets. The second partner Mrs. Munthoipah was a small Industry in manufacturing cakes, using biogas from compos for lighting and cooking at home. The problem was the residual biogas was not yet utilized maximum, the residue which is in the form of soil could be usefull as a fertilizer, because the substance of methane compos has already utilized for biogas. The role of the first partner is as an object that supervised and accompanied for production and marketing. while the role of second partner is as the supplier of raw ingredients fertilizer from the residu that called slurry. The results that have been achieved is (i) the modification of screw machine  and enumerator (ii) Granulator machines and (iii) the use of slurry for biogas.